Estimating the accumulation and re-accumulation of commercial tobacco, electronic cigarette, and cannabis waste based on a stratified random sample of census blocks - Georg E. Matt; Lydia Greiner; Kristina Tran; Joseph Gibbons; Michael Vingiello; Paula Stigler Granados; Ronald Shadbegian; Thomas E. Novotny (PLoS ONE, 2025)
We investigated the amount and distribution of waste generated by commercial tobacco, electronic cigarette, and cannabis (TEC) use to inform policy options aimed at mitigating the environmental harm caused by these products. Using disproportionate stratified random sampling, we selected 60 census blocks from the eight largest cities in San Diego County, California. We twice surveyed publicly accessible areas in these blocks to quantify TEC waste accumulation and its re-accumulation. All collected items were photographed, classified, geocoded, counted, and properly discarded. We identified demographic, land use, and behavioral data from public sources and direct observations. We modeled total cigarette butt quantities for all census blocks across the eight cities and found similar results for Round 1 (8.63 million) and Round 2 (8.66 million) collections. Single-use plastic cigarette filters were the primary contributor to TEC waste (94%). Total TEC waste counts and cigarette butt counts showed strong linear associations (r = +0.86 and r = +0.91). The area surveyed, land use category, resident demographics, smoking prevalence, and walkability explained 78% of the variance in cigarette butt count. The interval between Round 1 and 2 counts did not affect re-accumulation counts, suggesting that baseline TEC waste levels were re-established within 1–2 months after cleanup. Annually, we estimate up to 200 million cellulose acetate plastic filters may be discarded in public areas of the eight cities. Given the continuous deposition, vast quantity, heterogeneous distribution, and rapid re-accumulation of TEC waste after cleanup, increasing removal efforts alone are financially untenable and impractical downstream solutions for TEC waste. Community-wide policies (e.g., filter bans, outdoor smoking restrictions) and individual behavior changes (e.g., reduced smoking rates, proper disposal of cigarette butts) are necessary to effectively mitigate the environmental impact of TEC waste in urban settings.